Iron(III) coordination properties of ladanein, a flavone lead with a broad-spectrum antiviral activity - Martin-Benlloch, Xavier; Novodomská, Alexandra; Jacquemin, D.; Davioud-Charvet, Elisabeth; Elhabiri, M. (New journal of chemistry, 2018)
Ladanein, a 5,6,7-trihydroxylayted flavone was recently shown to display potent antiviral activities toward enveloped virus particles (e.g., hepatitis C virus, human immunodeficiency virus, vesicular stomatitis virus). Fe(III) coordination and pH were suggested to be critical for bioactivation steps triggering host cell entry inhibition. The Fe(III) complexation properties of ladanein and related analogues, such as negletein and salvigenin, were then studied in solution under quasi-physiological conditions using physico-chemical tools and provided important insights into their stability/reactivity in solution.